Ketahanan Luntur Kain Batik dengan Pewarna Alami Secang Menggunakan Metode Pencoletan - Rama Eka Yulpando; Andi Sudiarso Sudiarso (Syntax Idea, 2022)
Indonesia has many natural resources that have potential as natural textile dyes. One of these natural resources is sappan wood which produces a red color. In coloring there are two methods used, namely the method of dyeing and dipping. In its development there are several color dyeing which results are less stable and are easily faded. To determine the feasibility of the technique of picking up the sappan wood material, research will be carried out using experimental methods and testing the color fastness of the fabric. The result for the technique of picking red color from sappan wood gets a stable color. The washing and rubbing test got a score of 4-5 (dry and wet) or good, and for the sweat test it also got a good score of 4-5 (acidic) and 4 (alkaline). However, the results of the soap washing and staining tests were worth 3 (enough) but below the minimum requirements, namely 4 (washing) and 3-4 (staining).